Monkeypox virus: A future scourge to the Pakistani Healthcare system. (July 2022) - Mansoor, Hussain; Abbas, Samina; Rehan, Syeda Tayyaba; Hasan, Mohammad Mehedi
Abstract: Monkeypox is a rare viral infection that is mostly concentrated in the regions of Central and West Africa. During the last couple of weeks, reports of confirmed monkeypox cases in non-endemic countries such as the United Kingdom have alerted health authorities in Pakistan as well. Keeping in mind the devastating effects of the recent COVID-19 pandemic on the healthcare system of Pakistan, a subsequent monkeypox outbreak can be catastrophic. During the COVID-19 outbreak, the lack of financial resources and manpower exposed the vulnerability of the country's healthcare system. Therefore, it is imperative that relevant health authorities proactively work towards educating the public regarding effective precautionary measures that can keep them safe in the event of a monkeypox outbreak.